Comparative anthropometric and physical characteristics of youth football players at the various stages of an international football talent screening and selection program - Price, A.; Peltola, E.; Varamenti, E.; Bourdon, P.; Cable, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: This study compares the baseline anthropometric and physical performance characteristics of youth football players at the various levels of a four-stage international humanitarian football talent screening and selection project (Aspire Football Dreams) which aims to inspire hope in children in developing countries. Over the past 9 years, ~4.6 million boys from 19 developing countries across Africa, Asia and Latin America have registered for the project. This study includes data from the first 4 years of the project (2007-2010) as it takes a minimum 4 years to progress to Stage 4. Methods: Players were categorised based on the highest selection stage they achieved; Stage 1 - Country Finals (n=1823), Stage 2 - World Finals (n=49), Stage 3 - Educational and Sports Development Scholarship (n=64), Stage 4 -Professional Contract (n=20). Player progression was decided by a panel of coaches/staff based on a myriad of factors including technical, tactical, physical, psychological measures and predicted future potential. Only a limited number of players progress at any stage and they could opt to drop out at any time. Minimum age to progress to Stage 4 is 18 years old. Three anthropometric (height, seated height and body mass) and three physical performance measures (counter movement jump (CMJ) using a KMS jump mat, 40 m sprint with 10 m splits to assess peak velocity (m/s) using an electronic timing gate system, and a 20 metre multi stage shuttle run test) were assessed on all players during Stage 1. These measures were used for all subsequent analyses. Results: ANOVA analysis showed that players that progressed to Stage 3 were significantly (p 0.05); taller (167.5 vs. 171.1 cm), heavier (55.8 vs. 59.0 kg), faster (40 m sprint - 5.67 vs. 5.43 s), more powerful (CMJ - 37.1 vs. 39.9 cm) and displayed greater endurance (20 m Shuttle score - 11.55 vs. 12.45 level) than those players who did not progress beyond Stage 1. Those players selected to Stage 4 failed to show any significant differences from the other stages which is likely due to the relatively low number of players (n=20) progressing to this stage. Conclusion: These results suggest anthropometric and physical performance characteristics play an important role in the earlier stages of the selection program (Stages 1 to 3). However when it comes to the selection of players for a professional contract at Stage 4, other non-physical measures (i.e., technical skills, tactical understanding, personality, attitude etc.) become equally if not more important.